2021
DOI: 10.22270/jmpas.v10i3.1127
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Pulmonary Rehabilitation Program for the Management of Posttuberculosis Pneumothorax: A Case Study

Abstract: Pulmonary tuberculosis is a contagious disease of the lung caused by mycobacterium tuberculosis. The disease is curable and preventable, but its sequelae induce structural lung damage, physiological dysfunction resulting in disability, respiratory distress, and decreased exercise capacity affecting ADLs. Pneumothorax is considered to be a major complication of TB among all the known sequelae. In the present case, the patient complained of moderate dyspnea, chest pressure, and chest pain. Based on chest radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Other studies stated that pulmonary rehabilitation in pneumothorax patients can reduce the duration of hospitalization. 18,19 Segmental breathing exercises, thoracic expansion exercises, and pursed lip breathing techniques can reduce tightness, increase thoracic expansion, and restore lung function. [18][19][20] In this case, the patient improved, and there were no signs of recurrent pneumothorax for up to 3 months afterwards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies stated that pulmonary rehabilitation in pneumothorax patients can reduce the duration of hospitalization. 18,19 Segmental breathing exercises, thoracic expansion exercises, and pursed lip breathing techniques can reduce tightness, increase thoracic expansion, and restore lung function. [18][19][20] In this case, the patient improved, and there were no signs of recurrent pneumothorax for up to 3 months afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Segmental breathing exercises, thoracic expansion exercises, and pursed lip breathing techniques can reduce tightness, increase thoracic expansion, and restore lung function. [18][19][20] In this case, the patient improved, and there were no signs of recurrent pneumothorax for up to 3 months afterwards. Therapy response to anti-TB drugs was good, proven by decreased symptoms and increased body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Application of DMT in group therapy helps to reduce the CRF in breast cancer patients [9]. Previous research showed that a brief DMT intervention over the course of RT would benefit the patients by buffering their treatment-related symptoms while the symptoms would worsen in women who did not receive DMT [10,11].…”
Section: Introductionmentioning
confidence: 99%